O rewolucji, poezji i życiowych decyzjach Karola Wojtyły = On revolution, poetry and life decisions of Karol Wojtyla - Ołdakowska-Kuflowa, Mirosława (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this article beliefs of Karol Wojtyla - John Paul II about social issues expressed in his writings were subjected to an observation. Following literary works were subjected to this process: not intended for printing drama "Brother of our God" - dramatic composition inspired by person of Adam Chmielowski - saint brother Albert, and two poems "The Quarry" and "Easter Vigil of 1966".
Keywords: Jan Paweł II, papież (1929-2005); John Paul II